Keberlanjutan Sistem Penyediaan Air Minum Berbasis Komunitas (Studi Kasus: Hippam Mandiri Arjowinangun, Kota Malang) - Sri Maryati; Natasha Indah Rahmani; Anggit Suko Rahajeng (Jurnal Wilayah dan Lingkungan, 2018)
Limited capacity of government on drinking water supply has demanded the implementation of Community Based Water Supply System, one of them in the form of a Drinking Water User Association (Hippam). An important issue in community-based water supply is sustainability, from which institutions play a critical factor in the sustained provision of drinking water. Institutions relate to management, maintenance and financing systems, and contribute to technology selection and decision making. The purpose of this study is to explore the institutional conditions as a determinant factor for the sustainability of community-based water management. The study also aims to develop a framework for sustainable institutional assessment in community-based drinking water supply. In this study Hippam Mandiri Arjowinangun (HMA) in Malang City, East Java Province was chosen as a case study. HMA has been operating since 1994. The sustainability of HMA regarding applying the principles of institutional support for sustainability was very interesting as a case. The research method applied qualitative research by comparing the benchmark of institutional principles of sustainability with institutional principles applied to HMA. The result shows that HMA has applied the principles of institutional support for sustainability. However, some issues should be addressed in the HMA sustainability include the delineation of the water source boundary, specific attributes for the users, and the rules of water utilization. The study has also produced an assessment framework for the sustainability of community-based drinking water supply systems from the institutional perspective.